Investigation of the Cross Section of the Pile Foundation on the Combined Effect of Calculated Stresses on the Resistance of Materials.: Penelitian mengenai Penampang Tumpukan Fondasi pada Pengaruh Gabungan Beban Terhitung terhadap Ketahanan Material. - Maxmudovna , Ismatova Dilfuza; Xakimovna, Xaydarova Kamola (Indonesian Journal of Innovation Studies, 2024)
This study investigates the cross-sectional behavior of pile foundations under the simultaneous influence of bending moments, transverse and longitudinal forces, assessing calculated stresses in accordance with material resistance. The goals involve determining non-central compression or elongation in pile foundations due to the combined effects to evaluate cross-sectional resistance. Employing analytical methods, the study presents results revealing the intricate interplay of these forces on the foundation's behavior. The implication of this research lies in enhancing the understanding of pile foundation response to complex loading conditions, providing valuable insights for optimizing foundation design in diverse geotechnical contexts. Highlights: Integrated Analysis: Comprehensive investigation of pile foundations, considering the combined effects of bending moments, transverse and longitudinal forces, offering insights into their holistic behavior. Material Resistance Assessment: Evaluation of calculated stresses in pile foundations, determining non-central compression or elongation, contributing to a refined understanding of cross-sectional resistance. Optimization Implications: Implications for geotechnical engineering, providing valuable insights for optimizing pile foundation design under diverse loading conditions, with potential applications in real-world structural projects. Keywords: Pile foundations, Combined loading, Cross-sectional behavior, Material resistance, Geotechnical engineering.